2005
DOI: 10.1007/s10433-005-0021-x
|View full text |Cite
|
Sign up to set email alerts
|

Disability and social ties: comparative findings of the CLESA study

Abstract: The associations between prevalence, incidence and recovery from activities of daily living (ADL) disability and social ties among community-dwelling persons over 65 in Finland, The Netherlands and Spain are examined. Data were harmonized in the CLESA study. The baseline sample was composed of 3,648 subjects between 65 and 85 years old, living in Finland, The Netherlands and Spain. Disability in four activities of daily living was determined at baseline and at follow-up. Social participation, number of family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1
9

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 35 publications
1
41
1
9
Order By: Relevance
“…As discussed previously, various cohort studies have shown that social relations are determinants of future performance of ADL in the elderly 3,5,6,7,8,9,10,11,12,13,14 . Other cohort studies have shown that both emotional support 8 and size of total social network (especially the family network) 7 predict not only future functional limitation but also recovery from it, suggesting a bidirectional association.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…As discussed previously, various cohort studies have shown that social relations are determinants of future performance of ADL in the elderly 3,5,6,7,8,9,10,11,12,13,14 . Other cohort studies have shown that both emotional support 8 and size of total social network (especially the family network) 7 predict not only future functional limitation but also recovery from it, suggesting a bidirectional association.…”
Section: Discussionmentioning
confidence: 85%
“…Evidence suggests that cultural differences can modify social behaviors 29 , as well as satisfaction with life and friends 30 . Zunzunegui et al 9 assessed the influence of presence or absence of friends on the incidence and prevalence of functional limitation among elderly in three different countries (Finland, Netherlands, and Note: estimated percentages, considering the sampling parameters. Spain).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cerhan & Wallace 35 afirmam que a interação entre as relações sociais e a saúde é bidirecional: a piora no estado de saúde induz a uma restrição da rede social, enquanto um decréscimo nas redes sociais, de maneira repetida e prospectiva, prediz a mortalidade e morbidade graves. Isso ocorre tanto em estudos populacionais quanto em indivíduos com morbidade conhecida 36,37 e piora com a idade 39 . Um estudo multicêntrico conduzido na Finlândia, Holanda e Espanha, que comparou a prevalência, a incidência e a recuperação da incapacidade entre idosos que vivem na comunidade, demonstrou que ainda que existam diferenças culturais, os laços sociais (familiares e não-familiares) são protetores da incapacidade na velhice 39 .…”
Section: Características Predisponentesunclassified
“…Isso ocorre tanto em estudos populacionais quanto em indivíduos com morbidade conhecida 36,37 e piora com a idade 39 . Um estudo multicêntrico conduzido na Finlândia, Holanda e Espanha, que comparou a prevalência, a incidência e a recuperação da incapacidade entre idosos que vivem na comunidade, demonstrou que ainda que existam diferenças culturais, os laços sociais (familiares e não-familiares) são protetores da incapacidade na velhice 39 . Quando considerada a incidência da incapacidade, os laços familiares têm maiores efeitos protetores do que os laços não-familiares, mas quando considerada a prevalência da incapacidade, os laços não-familiares são mais protetores.…”
Section: Características Predisponentesunclassified